Restoration of Endodontically Treated Anterior Teeth with Cast Metallic Post or Prefabricated Fibre Post Placement: 2 Case Reports and Critical Literature Review - Tortopidis Dimitrios; Kourtis Stefanos; Kountouras Konstantinos (Balkan Stomatological Society, 2015)
With a wide variety of post systems and materials available for the restoration of lost tooth structure of endodontically treated teeth, the clinical decision of which to use constitutes a challenge to dental practitioners. Cast metal post and cores are widely used for restoring endodontically treated teeth with extensive loss of coronal tooth structure and to retain metal-ceramic crowns. When dental aesthetics is of primary concern, the selection of the underlying restorative material becomes an important factor to consider. The fibre-reinforced posts combined with all-ceramic crowns offer a highly aesthetic outcome in anterior region restorations, but longterm evaluation is necessary in order to assess their clinical performance and longevity.